Estimation Of The Genetic Parameters Of Eight Soybean Varieties In The Wasegi Village At Prafi District Manokwari Regency - Nouke L. Mawikere; Purbokurniawan Purbokurniawan; Alce Ilona Noya; Darius Dare (JERAMI : Indonesian Journal of Crop Science, 2020)
This study aims to estimate genetic parameters including genetic diversity coefficient, phenotypic diversity coefficient, heritability value, and the correlation between the character of plants from eight soybean varieties. The research was conducted from August to December 2017, in the Wasafi Village of Prafi District, Manokwari Regency. The study was designed using Randomized Block Design (RBD) with 8 treatments of soybean varieties. Each treatment was repeated 4 times, to obtain 32 experimental units. The data obtained were analyzed using ANOVA and if it had a significant effect, it was further tested using the Duncan Multiple Range Test (DMRT) at the 95% level, through the Costat program. The results of ANOVA analysis were used to obtain Variable Partition values, Genetic Diversity Coefficient (GDC), Phenotype Diversity Coefficient (PDC), and Heritability. Correlations between characters were also analyzed using the Costat program. Estimation results of genetic parameters indicate that the characters selected for selection criteria are based on the value of GDC, PDC, and high heritability are number of branches, number of fertile books, number of filled pods, and number of total pods. The characters that show a positive correlation with the character of the results are plant height, number of trifoliate leaves, harvest age, number of filled pods, number of empty pods, total pods, and number of seeds per plant, while characters that show a negative correlation to a seed weight character are flowering age.